Assessment of geothermal resource potential in Changbaishan utilizing high-precision gravity-based man-machine interactive inversion technology - Xu, Zhi-He; Jiang, Ji-Yi; Gu, Guan-Wen; Sun, Zhen-Jun; Jiao, Xuan-Kai; Niu, Xing-Guo; Yu, Qin (Frontiers in Big Data, 2023)
Geothermal resources, as one of clean energy, have no negative impact in changing climate energy. However, the accurate assessment and precisely identification the potential geothermal resource is still complex and changeable. In this paper, about 2,000 large-scale high-precision gravity survey points are conducted in the north of the Tianchi caldera, Changbaishan. New data processing technologies provide straightforward information deep geothermal resource (Hot source, caprock, geothermal reservoir and geothermal migration pathway). Upwards continuation and the first vertical derivative technologies decode two dome shape low and gentle anomalies (-48 × 10-5 m/s2 to -65 m/s2) and a positive gravity gradient anomaly (0.4 × 10-7 m/s2 to 1.6 × 10-5 m/s2) in large-scale high-precision gravity planar. According to two point five dimensional man-machine interactive inversion technology and the researches on petrophysical parameters, the density of shied-forming basalts in the two orthogonal gravity sections is 2.58 g/cm3. The relatively intermediate to high density (2.60 g/cm3 to 2.75 g/cm3) represents geothermal reservoir, and low density (low to 2.58 g/cm3) is the geothermal migration pathway. In addition, large-scale high-precision gravity planar with a solution about 1/50000 indicate that the north of the Tianchi caldera exits the sedimentary basin and uplift mountain geothermal system.